2021
DOI: 10.3389/fonc.2021.680691
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Various Forms of Contrast-Enhanced MRI for Diagnosing Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis

Abstract: BackgroundContrast-enhanced MRI can be used to identify patients with hepatocellular carcinoma (HCC). However, studies around the world have found differing diagnostic accuracies for the technique. Hence, we designed this meta-analysis to assess the accuracy of contrast-enhanced MRI for HCC diagnosis.MethodsWe conducted a systematic search for all studies reporting the diagnostic accuracy of contrast-enhanced MRI for HCC in the databases of MEDLINE, EMBASE, Cochrane Library, Web of Science, SCOPUS, ScienceDire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…MRI is an excellent modality for lesion detection and characterization thanks to its higher contrast resolution and ability to assess more tissue properties than sole vascularization. According to a recent meta-analysis, the pooled sensitivity and specificity for HCC diagnosis were 70% and 94%, respectively, regardless of tumor size [ 122 ]. However, sensitivity is greater for lesions >2 cm (approaching 100%) but drops to 58.3–64.6% for lesions smaller than 2 cm [ 123 , 124 , 125 ], and it is even lower for sub-centimetre lesions.…”
Section: Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is an excellent modality for lesion detection and characterization thanks to its higher contrast resolution and ability to assess more tissue properties than sole vascularization. According to a recent meta-analysis, the pooled sensitivity and specificity for HCC diagnosis were 70% and 94%, respectively, regardless of tumor size [ 122 ]. However, sensitivity is greater for lesions >2 cm (approaching 100%) but drops to 58.3–64.6% for lesions smaller than 2 cm [ 123 , 124 , 125 ], and it is even lower for sub-centimetre lesions.…”
Section: Mrimentioning
confidence: 99%
“…A small residual tumor can escape detection in this early stage, though growth on subsequent follow-up imaging, or the presence of “wash-out”, should raise suspicion for viable malignancy [ 213 ]. Although dynamic MDCT is the established method for following patients after thermal ablation, due to its wider availability, MRI might offer superior diagnostic accuracy and sensitivity for detection of recurrent HCC, especially with the use of diffusion-weighted images or liver-specific contrast media [ 122 , 214 ]. Few studies with small sample sizes have evaluated the role of CTLP in exploring the hemodynamic changes of HCC nodules after RFA [ 112 , 197 , 215 ].…”
Section: Imaging Assessment Of Hcc Following Percutaneous Locoregiona...mentioning
confidence: 99%
“…Meanwhile, controversies still remain regarding the diagnostic efficacy of HCC. Despite that the hepatobiliary agent-enhanced MRI is believed to reach an early diagnosis for HCC that is still in the hypovascular stage ( 94 ), researchers analyzed the clinical trials that use different contrast agents for HCC diagnosis and found no significant difference in the diagnostic efficacy in terms of sensitivity and specificity between the MRI using extracellular agents and hepatobiliary agents ( 95 , 96 ). Imbriaco et al.…”
Section: Clinical Challenges and Prospectsmentioning
confidence: 99%
“…43 The sensitivity and specificity of contrast-enhanced MRI for detecting HCC nodules are 70% and 94%, respectively. 44 However, the sensitivity drops to 60% for lesions <2 cm, and it is even lower for lesions <1 cm. 45 In our experiments, all HCC lesions (<1 cm) were detected by SP94-Fe3O4@ICG&DOX nanoparticles, which indicated our nanoparticles enhanced the detection sensitivity and had great potential in clinical diagnosis of HCC.…”
mentioning
confidence: 97%